International journal of physical distribution and logistics management, volume 45-4 : special issue. (International Journal of Physical Distribution & Logistics Management: Volume 45, Issue 4., 2015)
This ebook presents four specially selected papers from the 26th NOFOMA annual conference which took place at Copenhagen Business School, Denmark on 11-13 June, 2014. NOFOMA, the Nordic network of researchers in logistics and supply chain management, was originally established by universities in Norway, Sweden, Finland, and Denmark and was later augmented by universities in Iceland. Today, the conference enjoys considerable popularity far beyond the Nordic countries, attracting attendees from many parts of the world every year. The papers presented are da Mota Pedrosa, Blazevic and Jasmand: ""